Efektifitas Penambahan Curd Kefir terhadap Mutu Sabun dan Daya Hambat Pertumbuhan Escherichia coli pada Sabun Alami Berbahan Dasar Tallow - D T Marya; A Sofiana; N A Usman (Politeknik Negeri Lampung, 2022)
The ban on using triclosan as an antiseptic in bath soap in various countries has given rise to new ideas to apply natural ingredients as an alternative. Curd kefir, as a natural ingredient, can be used as an alternative antiseptic. In this study, the manufacturing of tallow-based soap has been developed by adding kefir curd as an antiseptic to improve the soap's quality and inhibit the growth of Escherichia coli. The results showed no significant difference in the soap's free alkali content, saponification number, and hardness. The inhibition of the growth of Escherichia coli increased with the rise of kefir curd concentration.